Evolution of postoperative care: marked reduction of opioid consumption when ERAC pathway added to wound soaker therapy for cesarean delivery. (31st December 2023) - Masaracchia, Melissa M.; Zaretsky, Michael V.; Pan, Zhaoxing; Zhou, Wenru; Chow, Franklin S.; Wood, Cristina L.
Abstract: Objective: Achieving functional recovery after cesarean delivery is critical to a parturient's ability to care for herself and her newborn. Adequate pain control is vital, and without it, many other aspects of the recovery process may be delayed. Reducing opioid consumption without compromising analgesia is of paramount importance, and enhanced recovery pathways have generated considerable interest given their ability to facilitate this. Our group's process for reducing opioid consumption for cesarean delivery patients evolved over time. We first demonstrated that providing additional incisional pain control with continuous bupivacaine infusions through wound catheters, with the concurrent use of neuraxial morphine, reduced postoperative opioid use. Iterations of an enhanced recovery after cesarean (ERAC) delivery pathway were then implemented after the Society for Obstetric Anesthesia and Perinatology's consensus statement for ERAC was issued to eliminate variability in both hospital course and in the treatment of postoperative pain. In this retrospective cohort analysis, we sought to identify whether adding ERAC protocols to our existing combination of neuraxial morphine and wound soaker catheters further reduced opioid consumption after cesarean delivery. Methods: A retrospective cohort analysis of cesarean deliveries from 2015 through 2020 was performed. Deliveries were divided by analgesic pathway into four time-periods – time-point 1 [January 2015-April 2016, previous standard of care (control, N = 61)]: neuraxial morphine in addition to as needed opioid and non-opioid analgesics; time-point 2 [May 2016–May 2019, introduction of wound soaker (wound-soaker, N = 40)]: continuous wound catheter infusions of local anesthetic, neuraxial morphine in addition to as needed opioid and non-opioid analgesics; time-point 3 [May 2019–December 2019, wound soaker + early ERAC pathway (early ERAC, N = 78)] : continuous wound catheter infusion of local anesthetic, neuraxial morphine, in addition to scheduled non-opioid analgesics (acetaminophen and ibuprofen) every 6 h, alternating in relation to one another so that one is given every 3 h; time-point 4 [January 2020–July 2020, wound soaker + late ERAC pathway (late ERAC, N = 57)]: continuous wound catheter infusion of local anesthetic, neuraxial morphine in addition to non-opioid analgesics scheduled together every 6 h (to facilitate periods of uninterrupted rest). Cumulative and average daily opioid use for postoperative days (POD) 1–4 were analyzed using ANOVA and a mixed effect model, respectively. Results: Average daily opioid consumption and total cumulative opioid consumption POD 1–4 (morphine milligram equivalents) for both early and late ERAC groups (23.9 ± 31.1 and 29.4 ± 35.1) were significantly reduced compared to control and wound soaker groups (185.1 ± 93.7 and 134.8 ± 77.1) ( p  < .001). Conclusion: The addition of ERAC protocols to our standardized multimodal analgesic regimen (local anesthetic wound infusion catheters and neuraxial morphine) for cesarean delivery significantly reduced postoperative opioid consumption.